Avaliação da viabilidade econômica da implantação de uma usina de triagem e compostagem na cidade de Rio Claro-SP - Salomão, Fernanda Sota [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
The question of the solid waste is without a doubt one of the biggest problems faced for the world-wide population in the present time, resulting in the call “collapse of the garbage”. In this direction that appears the composting, in the scope of the treatment of organic waste origin, that in Brazil, approximately correspond 50% of the generated volume. However, the rare plants of selection and composting (UTC) existing at least do not obtain auto-to support themselves, increasing to each day the number of deactivations, almost always related the financial questions. In this direction, the present research brings the analysis of the economic viability of the implantation of a UTC for the city of Rio Claro-SP, relating it with the thick organic composition sales, for the cultures of vegetables cultivated in a ray of 30 km of the study area. For in such a way, they had been carried through, calculations concerning the regional demand for organic composition, and the verification of the implantation costs and operation of the plant. The reached results had been the flow of box for the first year of functioning of the UTC, as well as the break-even point between the gotten expenditures and prescriptions. From this relation investment profitability, it was verified that the UTC is presented impracticable under the economic point of view.

A questão dos resíduos sólidos é sem dúvida um dos maiores problemas enfrentados pela população mundial na atualidade, resultando no chamado “colapso do lixo”. È neste sentido que surge a compostagem, no âmbito do tratamento de resíduos de origem orgânica, que no Brasil, correspondem a aproximadamente 50% do volume gerado. Porém, as raras usinas de triagem e compostagem (UTC) existentes não conseguem sequer se auto-sustentar, aumentando a cada dia o número de desativações, quase sempre relacionadas a questões financeiras. Neste sentido, a presente pesquisa traz a análise da viabilidade econômica da implantação de uma UTC para a cidade de Rio Claro-SP, relacionando-a com a venda de composto orgânico grosso, para as culturas de hortaliças cultivadas em um raio de 30 km da área de estudo. Para tanto, foram realizados, cálculos acerca da demanda regional por composto orgânico, e a verificação dos custos de implantação e operação da usina. Os resultados alcançados foram o fluxo de caixa para o primeiro ano de funcionamento da UTC, bem como o ponto de equilíbrio entre as despesas e as receitas obtidas. A partir desta relação investimento/ lucratividade, verificou-se que a UTC apresenta-se inviável sob o ponto de vista econômico.
Keywords: Engenharia sanitaria; Resíduos sólidos; Avaliação econômica; Compostagem; Solid waste; Composting; Economic assessment